Thinking about thinking: the mind's porosity and the presence of the gods. (25th March 2020) - Luhrmann, T.M.
Abstract: The Mind and Spirit project found that the way a social world invites its members to experience thought appears to have consequences. When the boundary between inner awareness and outer world is culturally represented as porous, so that thoughts can be construed to move in and out of the mind as if they had agency and power, people are more likely to describe their experience of invisible others as if those others could be experienced with the senses. They are more likely to say that a god or spirit spoke in a way they could hear with their ears, or that they sensed a presence in the room. Abstrait: Penser la pensée : porosité de l'esprit et présence des dieux Résumé Le projet « Esprit et Esprit(s) » a permis d'observer que la manière dont un monde social invite ses membres à appréhender la pensée semble avoir des conséquences. Quand la frontière entre conscience intérieure et monde extérieur est représentée, culturellement, comme quelque chose de poreux, où l'on peut imaginer que les pensées entrent et sortent de l'esprit comme si elles étaient dotées d'agencéité et de pouvoir, les sujets sont davantage enclins à décrire leur perception d'autres invisibles comme si ces autres pouvaient être perçus par les sens. Ils disent plus souvent qu'ils ont entendu « de leurs oreilles » un dieu ou un esprit parler ou qu'ils ont senti une présence dans une pièce.